2018
DOI: 10.4269/ajtmh.17-0889
|View full text |Cite
|
Sign up to set email alerts
|

Dried Blood Spots for Global Health Diagnostics and Surveillance: Opportunities and Challenges

Abstract: Abstract.There is increasing interest in using dried blood spot (DBS) cards to extend the reach of global health and disease surveillance programs to hard-to-reach populations. Conceptually, DBS offers a cost-effective solution for multiple use cases by simplifying logistics for collecting, preserving, and transporting blood specimens in settings with minimal infrastructure. This review describes methods to determine both the reliability of DBS-based bioanalysis for a defined use case and the optimal condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
152
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(155 citation statements)
references
References 147 publications
2
152
0
1
Order By: Relevance
“…Blood is the most used biofluid for clinical tests and for research purposes, as it can often indicate the health status of an individual. Although the most common method of blood collection is venipuncture, microsampling methods, requiring Ͻ100 l of blood, such as capillary blood sampling, are gaining acceptance (1). The dried blood spot (DBS) 1 microsampling technique has already been found to be useful for both population-wide screening and in research studies, as indicated by the total number of analytes currently measurably (using a variety of analytical methods and numerous assays), including 1001 small molecules, 677 large molecules (proteins), 309 nucleic acids and 31 elements (2).…”
mentioning
confidence: 99%
“…Blood is the most used biofluid for clinical tests and for research purposes, as it can often indicate the health status of an individual. Although the most common method of blood collection is venipuncture, microsampling methods, requiring Ͻ100 l of blood, such as capillary blood sampling, are gaining acceptance (1). The dried blood spot (DBS) 1 microsampling technique has already been found to be useful for both population-wide screening and in research studies, as indicated by the total number of analytes currently measurably (using a variety of analytical methods and numerous assays), including 1001 small molecules, 677 large molecules (proteins), 309 nucleic acids and 31 elements (2).…”
mentioning
confidence: 99%
“…However, obscure DBS failures, such as hematocrit or blood cell count variations, are difficult to assess. 15 Reduced LAL activity was documented in individuals with advanced liver disease, including cryptogenic cirrhosis and cirrhosis of known etiology, who had lower WBC and PLT counts than control subjects. 10 Moreover, a direct correlation between WBC and PLT counts and LAL activity in DBS from healthy individuals has been described.…”
Section: Discussionmentioning
confidence: 98%
“…In 4.3% of the examined DBS, we observed a low LAL activity without detectable LIPA alterations. A reduced enzymatic activity in DBS is usually ascribed to poor specimen quality . DBS with gross preparation errors, such as clotting, disturbed integrity, low volume, and microbiological contamination, can be detected by visual inspection and excluded from analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations